Emulsified fuel performance on compression ignition engine. - Manegdeg, Ferdinand G.
The research aims to show the performance of using emulsified fuel in a compression ignition engine. Diesel and four (4) fuel mixtures consisting of different proportions of diesel, bunker water and catalyst were tested at various storage durations and engine parameters. A batch mixer was designed and fabricated to blend the fuel mixtures. It was observed that the thermal efficiency was lower when firing the engine with fuel mixtures of diesel, bunker, water and catalyst than when firing the engine with straight diesel. The research however, proves that the fuel mixtures can be used as alternative fuels without engine modifications. There is no substantial difference on the engine performance for all the tested fuels at various storage durations.